PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS BLOG BAGI MAHASISWA - Rika Ariyani; Nur Anisyah; Darni Darni (Yayasan Literasi Kita Indonesia, 2022)
As professionals, lecturers must be able to use and utilize media to support the learning process. Through the use of learning media, the presentation of the material becomes easier. Various types of learning media that can be used, one of which is a blog media. Apart from being free and not acknowledging space and time, blogs are a very efficient communication medium so that lecturers and students can interact such as asking questions, discussing and soon. In addition, blog-based learning media are also more flexible, lecture materials can be presented in attractive forms such as videos, pictures, and also PPT. Blog-based learning media is not only beneficial for students but also for the lecturers themselves. The blog is proof of his professionalism. Through blogs, lecturers can also indirectly improve their quality to be more creative, hone lecturers' skills in literacy, and can add insight.